2022
DOI: 10.1021/acsomega.2c05836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quercetin and Organically Modified Montmorillonite on the Properties of Poly(butylene adipate-co-terephthalate)/Thermoplastic Starch Active Packaging Films

Abstract: The poly(butylene adipate-co-terephthalate) (PBAT)/thermoplastic starch (TPS) film stands out owing to its acceptable price, low impact on the environment, and excellent mechanical properties. The main objective of this study was to improve the antioxidant properties of the PBAT/TPS film by incorporation of quercetin (Q) through the extrusion blow process. Another specific objective was to incorporate the organically modified montmorillonite (OMMT) to prolong the release of Q and improve the poor barrier prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Some studies with montmorillonite and halloysite clays have shown significant changes in antioxidant properties when incorporated into biopolymer materials [20,21]. However, based on our research, there are no existing reports in the literature regarding the use of Laponite clay as a natural biopolymer modifier to enhance the antioxidant properties of materials when applied to food packaging.…”
Section: Introductionmentioning
confidence: 75%
“…Some studies with montmorillonite and halloysite clays have shown significant changes in antioxidant properties when incorporated into biopolymer materials [20,21]. However, based on our research, there are no existing reports in the literature regarding the use of Laponite clay as a natural biopolymer modifier to enhance the antioxidant properties of materials when applied to food packaging.…”
Section: Introductionmentioning
confidence: 75%
“…PBAT film after incorporating curcumin showed effective antioxidant and antibacterial activity, and its water vapor barrier was improved 35 . The composite films after the addition of quercetin into PBAT/thermoplastic starch through extrusion blow molding, showed enhanced antioxidant and UV resistance, with an oxygen barrier of up to 94% 36 . In addition, it is reported that the biological nanocomposites of cumin essential oil/PBAT/organic clay were prepared by solvent casting approach, which exhibited improved UV barrier performance, antibacterial and antioxidant activity 37 …”
Section: Introductionmentioning
confidence: 99%
“…35 The composite films after the addition of quercetin into PBAT/ thermoplastic starch through extrusion blow molding, showed enhanced antioxidant and UV resistance, with an oxygen barrier of up to 94%. 36 In addition, it is reported that the biological nanocomposites of cumin essential oil/PBAT/organic clay were prepared by solvent casting approach, which exhibited improved UV barrier performance, antibacterial and antioxidant activity. 37 In our previous works, some natural substances have shown strong antioxidant activity, such as bamboo leaves, 38 punica granatum peel, 39 pine needle, 40 puerarin, 41 forsythia suspense, 42 and scutellaria baicalensis.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental concerns regarding plastic food packaging waste have recently increased, with both packaging manufacturers and consumers becoming more conscious of the use of petroleum-based plastic films. ,, The development of biodegradable films made from natural resources offers a solution to the critical problem of plastic waste disposal, replacing fossil-oil-based packaging materials. Biodegradable polymer packaging, such as poly­(butylene succinate) (PBS) and poly­(butyrate adipate terephthalate) (PBAT), has gained traction due to favorable processability and excellent mechanical and biodegradable properties. These materials are appropriate for packaging applications, but one drawback associated with biodegradable polymer packaging is the inherently low gas permeability, limiting its suitability for preserving the freshness of perishable commodities. , Gas permeability of biodegradable plastic films can be improved by using laser perforation technology. , When a laser beam is directed onto the film surface, energy is absorbed, generating heat that melts and removes the plastic material, resulting in the formation of small holes. Microperforated films are now used in the packaging of fresh food products using MAP. ,,,, This cost-effective technique enhances the gas transport properties of the packaging films by introducing microperforations as tiny holes with diameter of less than 300 μm .…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymer packaging, such as poly(butylene succinate) (PBS) and poly(butyrate adipate terephthalate) (PBAT), has gained traction due to favorable processability and excellent mechanical and biodegradable properties. 15 17 These materials are appropriate for packaging applications, but one drawback associated with biodegradable polymer packaging is the inherently low gas permeability, limiting its suitability for preserving the freshness of perishable commodities. 18 , 19 Gas permeability of biodegradable plastic films can be improved by using laser perforation technology.…”
Section: Introductionmentioning
confidence: 99%